Study of Analgesic activity Siddha formulation vatha siletpana sura kudineer- in vivo study - Prasad, V.M.; Duraichi, A. (Govt. Siddha Medical College, palayamkottai, Tamilnadu, India, 2023)
Siddha medicine is an ancient Tamil medicine and it describes about various types of medicines for various treatments. To prove its efficacy it is essential to prove the medicinal uses through modern techniques. Vatha Siletpana sura kudineer is a herbal siddha formulation which is used mainly to treat viral fevers. Viral infection causes many symptoms and among them pain is an important symptom. During viral infected fever, pain includes throat pain, abdominal pain, shoulder pain, head ache, back ache, and whole body pain may occur. The Siddha formulation vatha siletpana sura kudineer relieve the pain caused by viral fever. Aim of this study is to analyze the analgesic activity of the medicine. Analgesic activity was done using wister rats which are divided into four groups and each group received a particular treatment and placed in the on Eddy’s hot plate kept at a temperature of 55±0.5 degree Celcius. . Reaction time was recorded when animals licked their fore or hind paws, or jumped prior to and 0, 30, 60 and 90 min after oral administration of the samples. The results of statistical analysis for animal experiment were expressed as mean ± SEM and were evaluated by ANOVA followed by Dunnet’s multiple comparisons. The results obtained were compared with the vehicle control group. The p<0.05, 0.001 were considered to be statistically significant. The Siddha herbal Formulation vatha siletpana sura kudineer doses showed significant analgesic action compared to the reference drug diclofenac sodium but drug 200 mg /kg was found to exhibit higher analgesic activity.
Keywords: Analgesic; Siddha formulation; Kudineer; In-vivo